2008
DOI: 10.1292/jvms.70.1027
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison Between Injection Speed and Iodine Delivery Rate in Contrast-Enhanced Computed Tomography (CT) for Normal Beagles

Abstract: ABSTRACT. The purpose of this study was to compare between the injection speed and iodine delivery rate in order to establish a concept for reproducible contrast timing in contrast-enhanced computed tomography (CT) for small animals. Clinically healthy beagle dogs were administered a nonionic iodinate contrast medium at a dose of 800 mgI/kg; they were divided into 3 groups (n=5, crossover method): in one group, the injection speed was fixed at 1.0 ml/sec, and in the second and third groups, the iodine delivery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 9 publications
0
6
0
1
Order By: Relevance
“…The results of this study showed that the CT images of the portal phase and hepatic parenchymal phase are influenced to a relatively lesser degree by injection duration in the multi-phase CT scan. However, a longer injection duration of 30 and 60 sec resulted in differences in the hepatic parenchymal enhancement peak in a veterinary study [30]. In previous veterinary literature, although the start of the portal phase cannot always be set at the PVP by the inter-scan reset, it has been reported that the variation does not affect scan quality [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study showed that the CT images of the portal phase and hepatic parenchymal phase are influenced to a relatively lesser degree by injection duration in the multi-phase CT scan. However, a longer injection duration of 30 and 60 sec resulted in differences in the hepatic parenchymal enhancement peak in a veterinary study [30]. In previous veterinary literature, although the start of the portal phase cannot always be set at the PVP by the inter-scan reset, it has been reported that the variation does not affect scan quality [32].…”
Section: Discussionmentioning
confidence: 99%
“…Among these, the injection duration of the contrast material is a major injection-related factor influencing contrast enhancement timing in CT [230]. In veterinary literature, arrival times to the aortic enhancement peak (AEP) and hepatic parenchymal peak (HPP) following 30 and 60 sec injection durations of contrast material have been reported [30]. In addition, the optimal diagnostic scan delay of the arterial and pancreatic parenchymal phases was recently investigated using a fixed injection rate of contrast material [10].…”
Section: Introductionmentioning
confidence: 99%
“…Following the non‐contrast CT study, contrast material was administered in 24 dogs, 800 mgI/kg iohexol (Omnipaque, Daiichi Sankyo, Japan) injected using an autoinjector (Autoenhance A‐60, Nemoto Kyorindo, Tokyo, Japan). Postcontrast CT was performed with the same slice thickness and body regions as for the non‐contrast CT scan, 1 minute after starting of the administration of the contrast material (Tateishi and others 2008).…”
Section: Methodsmentioning
confidence: 99%
“…The mean MEV in the maxillary artery was 244.45 HU with the saline chaser, and 202.29 HU without the saline chaser. In previous studies, the range of contrast attenuation values in dogs where a saline chaser was not used was 292 to 387 HU in the aorta (Kishimoto and others 2008, Tateishi and others 2008). Despite the relatively low blood volume per body weight of cows compared with dogs (Swenson 1993), the contrast enhancement effect in cows is lower than in dogs.…”
Section: Discussionmentioning
confidence: 99%